Legacies of Tortured Sensibility; or, what Shakira learned from Sade - Wennerstrom, Courtney (Romanticism and Victorianism on the Net)

(untitled) (Université de Montréal, 2011)
Apropos of the title, this essay traces the surprising connections between the eighteenth-century pornographer and the contemporary Latina superstar’s portrayals of eroticized torture, as well as elucidates the cultural significance of what I am calling a legacy of tortured sensibility. By illuminating how the gendered spectatorial politics of sensibility—particularly in its fetishization of the (female/feminized) body in pain—continues to inform the numerous interlocking discourses of race, gender, and sexuality we have inherited from Sade’s Europe, and especially from the early sentimental novel, this paper demonstrates how the transnational artist taps into a Sadean resistance to figurations of distressed hearts and flayed skin as sites of geopolitical and individual transcendence. Finally, examining 120 Days of Sodom and “La Tortura” side by side revitalizes attention to the ethical crisis surrounding aesthetic voyeurism: where does the anguish of reading Sade—with his relentless scenes of corporeal torment—go?